Religiusitas Magis Pura Taman Sari Desa Adat Sandakan Kecamatan Petang Kabupaten Badung - Sugiarta, I Putu (Metta : Jurnal Ilmu Multidisiplin, 2022)
Religion is a concept of religious order between human and God. A religious attitude, of course, based on the scriptures, which always obeys what He commands and stays away from all the prohibitions. One form of religious attitude is seen in the worship of God Almighty. Hinduism as one of the religions in Indonesia, of course, has its own way of worshiping Ida Sang Hyang Widhi / God with what is contained in the teachings of the Hindu holy book, the Vedas. One of the holy places in Hinduism is the Pura. Based on the type of temple, there is what is called the Dang Khayangan Temple, which is a temple made to worship the greatness of God and to commemorate the services of holy people who have spread the teachings of Hinduism. Taman Sari Temple is one of the Dang Khayangan Temples located in Sandakan Traditional Village, Sulangai Village, Petang District, Badung Regency which is a temple that is trusted by the surrounding community as a holy place to worship God and a place to ask for success in studying. The purpose of this research in general is to provide information to the public in order to know about the magical religiosity of Taman Sari Temple in the Sandakan Traditional Village. In addition, this research also aims to contribute knowledge and insight, especially in science related to the magical religiosity of temples. The method used in this research is qualitative research. Sources of data used are primary data, namely conducting direct interviews with informants who know and secondary data, namely related library sources, techniques for determining informants using snowball sampling, and data collection techniques using observation, interviews and documentation. The result of this research is that the magical religiosity of Taman Sari Temple is used as a place to ask for fluency in studying and helping find a mate and is used as a series of pawiwahan ceremonies for the local community. Taman Sari Temple also has functions, namely 1) social function, Taman Sari Temple is used as a place for social interaction such as during piodalan ceremonies, meetings and other dialogues. 2) aesthetic function, Taman Sari Temple is a manifestation of the creativity of the local community such as the architecture of the temple building, reringgitan on banten, sacred chanting, to dance and percussion. In addition to its function, Taman Sari Temple also has a theological meaning, namely worship of God Almighty who manifests as Lord Shiva with the identity of Ida Nak Lingsir at Taman Sari Temple. So knowing and understanding magical religiosity can increase the attitude of trust and belief in God.